Endodontic management of open apex using Biodentine as a novel apical matrix - Ambica Khetarpal; Sarika Chaudhary; Sangeeta Talwar; Mahesh Verma (Wolters Kluwer Medknow Publications, 2014)
Aim: Endodontic management of open apex using Biodentine as an apical matrix. Summary : An immature tooth with pulpal necrosis and periapical pathology imposes a great difficulty to the endodontist. Endodontic treatment options for such teeth consist of conventional apexification procedure with and without apical barriers. Biodentine™ is new calcium silicate based cement that exhibits physical and chemical properties similar to those described for certain Portland cement derivatives. This article demonstrates the use of the newer material, Biodentine as an apical matrix barrier in root end apexification procedure. This case reports present apexification and successful healing with the use of Biodentine as an apical barrier matrix. Conclusion : Apexification in one step using an apical plug of Biodentine can be considered a predictable treatment and may be an alternative to mineral trioxide aggregate apexification.